Agile business leadership methods for industry 4.0 - Akkaya, Bülent, 1979- (Emerald Publishing Limited, 2020)
Agile Business Leadership Methods for Industry 4.0 is a collection of innovative research on new leadership styles that will develop agile managers and business leaders who can improve company success in the fast-paced environments created by Industry 4.0.- Resumé vydavatel